Create your own hedge fund : - Wolfinger, Mark D. (John Wiley & Sons, 2005)
Create Your Own Hedge Fund explains how exchange-traded funds can be used in conjunction with an options strategy to attain steady growth. Beginning with a tutorial on options and ETFs, the book goes on to describe both investment approaches in great detail providing you with a trading strategy that generates higher returns than buy-and-hold investing -- and allows you to reduce risk by adopting a hedging strategy. Filled with in-depth insights and expert advice, this book is intended for you if you're a sophisticated individual investor or a professional investor, trader, or other money manager looking to update your arsenal of investment tools.